SYNTHESIS, CHARACTERIZATION AND STUDY THE EFFECT OF Te ON CRITICAL TEMPERATURE OF Tl-Re BASED CUPRATES. (International Journal of Scientific Research and Management (IJSRM), 2014)
In the present work, we presented the synthesis, characterization and study the effect of Te on Critical Temperature Tl-Re based Cuprates: one was Re-doped and another one was simultaneously doped with Te and Re. All these materials were prepared by the usual solid-state reaction method. Ba-CaCu-O precursors were made by taking BaCO3, CaCO3 and CuO in the ratio of 2:2:3. The Tl-Re based cuprate with the formal composition Tl1.88 Re0.12Ba2Ca2Cu3O10+δ was formed by adding stoichiometric amount of Tl2O3 and Re2O7 to the precursor and whole mixture was synthesized under closed condition at 950o C. For Tellurium doping, Tl2O3, TeO2, and Re2O7 were taken in the ratio of 1.85:0.03:0.12 and synthesized at the same condition .The samples are then palletized and annealed at oxygen environment. The Tellurium doping increased the critical temperature from 86K to 123K. X-ray diffraction reveals the presence of a number of more superconducting phases in Tl-Re-Te compounds. The gain homogeneity of the powered samples were excellent.